Expression of Cathepsin L in tumor cells and tumor-associated macrophages in patients with Ewing sarcoma family of tumors: A pilot study - Bivas Biswas; Mehar Chand Sharma; Asit Ranjan Mridha; Sameer Bakhshi (Wolters Kluwer Medknow Publications, 2015)
Background: Cysteine protease Cathepsin L is involved in bone remodeling and expressed in activated macrophages. It is highly expressed in metastatic tumor tissue, especially with bone metastases. Aims: We evaluated immunohistochemical expression of Cathepsin L in tumor cells and tumor-associated macrophages (TAMs) in chemo-naive Ewing sarcoma. Settings and Design: Retrospective evaluation of archived specimens of Ewing sarcoma. Materials and Methods: Immunohistochemical staining was performed on archived blocks of chemo-naive patients with Ewing sarcoma treated with uniform chemotherapy at our institute between January 2009 and November 2011. Statistical Analysis: Immunohistochemical expression was co-related with baseline demographics and survival. Results: During the study period, we had evaluable baseline samples from 62 patients with median age 15 years (range: 2-40); 26 (42%) had metastases. Cathepsin L expression in tumor cells was observed in 8/62 (13%) specimens. None of the baseline clinical characteristics correlated with Cathepsin L expression. Cathepsin L positivity was associated with poor response to neoadjuvant chemotherapy (NACT) (P = 0.05), but did not influence either event-free-survival (EFS) or overall survival. Cathepsin L was expressed in TAMs in all specimens. Grade 3 TAMs (>10 TAMs/high power field) was associated with better response to NACT (P = 0.05). On univariate analysis Grade 3 TAMs predicted superior EFS (median EFS 28.5 months in those with Grade 3 TAMs versus 14.8 months in those with grade ½ TAMs [P = 0.04]). Conclusions: Cathepsin L expression by immunohistochemistry was low in our patient cohort, and it did not affect the outcome. In addition, Grade 3 TAMs with Cathepsin L expression was associated with improved EFS.